DEEP BREATH RELAXATIONAND AUTOGENIC RELAXATIONTO THE RESPONSE SCALEOF PAINON POST CAESAREAN SECTION WOMEN - Eny Kusmiran; Lisbet Octovia Manalu; Diah Umanah (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction: Childbirth Caesarean section affects the health status of the mother and baby. Risks that may occur bleeding, thromboembolism and infection during the postpartum period. One ofnon-pharmacological therapies aimed at reducing the pain is deep breath relaxation techniques and autogenic relaxation. Autogenic relaxation techniques provide a calming effect on the body and mind, relaxation and deep breathing is a form of nursing care to relaxing body.Method: This study was a quasy experiment with non-randomized design with a pretest-post test control group design. The treatment was deep breathing relaxation techniques and autogenic. Analysis of the data was paired T-test. Results:Average pain response from a group of pre-relaxation breath is 5.57, and the average pain response of the mother after relaxation breath is 4.43. There is a reduction in pain after the relaxation response in the airway at 1:14. No statistically significant difference between the average pain response before the deep breathing relaxation intervention. In the group of mothers with autogenic relaxation obtained average the pain response before intervention is 5.57, and pain response after intervention autogenic relaxation is 3.67. There is a decrease in pain response after intervention with the average reduction was 1.9. No statistically significant difference between the average pain response before had the intervention autogenic relaxation. There was differences in the mean difference in pain response were significant between the groups of women with deep breathing relaxation treatment and with autogenic relaxation, where the pain response scores (1.143) in the group of mothers with deep breathing relaxation lower than the pain response scores (1.905) in the group of mothers with autogenic relaxation. Discussion: Deep breathing relaxation and autogenic relaxation decrease the pain response on post caesarean section women. They were significants average pain response between treated mother by deep breath relaxation and autogenic relaxation. Keywords: autogenic relaxation techniques, deep breathing relaxation techniques